Factors affecting the psychology of spectator inside of the sports stadiums: An analytical framework for managing sports crowds in Saudi stadiums - Osra, Oumr Adnan; Zaini, Lubna Mahmoud; Andejani, Emtinan Muhammad Nour; Aldadi, Bedour Mossem; Alsaaedi, Abeer Abid; Almalki, Sabah Jamaan; Sindi, Malak Talal (Journal of Economic, Administrative and Legal Sciences, 2022)
The study paper aimed to know the factors affecting the psychology of the Saudi sports fans in stadiums; The study population consisted of football fans in Saudi Arabia in one of the matches in the city of Jeddah, where the number of the audience was estimated (17000), the study sample represented (650) fans from different age groups and from different regions in the Kingdom, and they were chosen in a random way. The researchers reached a set of results, the most important of which is that the basic elements of crowd management from the fans’ point of view were of high importance. And that the theories explaining crowd psychology from the fans’ point of view were of great importance as well. also, the factors affecting the psychology of the spectators in the sports stadiums from the viewpoint of the fans were of medium importance. The study concluded with many recommendations, the most important of which is that event management and organization depends on planning, coordination and direct communication between all parties concerned with organizing the event, which has a direct impact on the psychology of individuals within crowds in sports stadiums. The study recommended the establishment of training courses for individuals in all bodies concerned with managing and organizing sporting events in various fields to deal with the behavior of the public and manage it in a safe manner.